ИСЛАМ ДИНИНИҢ ЖӘМИЙЕТИМИЗ ТУРМЫСЫНДАҒЫ ӘҲМИЙЕТИ - Упаев, Т. (ILIM hám JÁMIYET, 2020)
Humanity, kindness and mercy, mutual sympathy, honesty and faith in the underworld, these features of the religion of Islam are deeply rooted in the people. Religion makes a person better, happier, because in everything that for unbelievers are simply an event or a fact, the believer sees the contentment, mercy and blessing of the Most High. Islam encourages the acquisition of knowledge and training. The correct explanation and interpretation of this religion for the younger generation plays an important role in society.